G142(P) Prognosis for childhood CFS is excellent. (May 2019) - Robertson, D; Mansfield, K; Dennis, H; Wilson, C; Kumar, Y
Abstract : Aims: Services for childhood Chronic Fatigue Syndrome (CFS) are variable across the UK. We evaluated the service and outcomes involving an Occupational Therapy (OT) service commissioned to support children with CFS in the South-West of England. We also evaluated the demographics of the service users, looking at aetiology, gender and age. Methods: Patients up to 16 years of age were identified from the CFS Therapist database with data collected from that database along side hospital electronic patient records. All patients who presented for treatment between April 2014 to March 2018 were assessed for suitability. The inclusion criteria used for selecting participants included patients aged 16 or under, diagnosed with CFS, who had attended the CFS service at least once during this period. Results: 116 patients are in the study over the 4 year period April 2014-March 2018. Annual Incidence of CFS is 0.4 per 1000 children with male:female ratio of 2:3 with 81% being above 10 years of age. 36.2% of the patients had no precipitating cause identified with 40.7% reporting a recent viral infection. 47.9% of the viral infections were identified as Epstein Barr Virus (EBV). Medication use such as Amitriptyline, Gabapentin and melatonin was noted in 29.4%. 65.5% of the patients were discharged from both the CFS service and the paediatric team with 9.5% of the children transitioned to the adult team, all of whom had a diagnosis at a mean age of 13 years. Conclusion: Incidence of CFS in Cornwall is higher compared to reported rates across the West (0.11). As has been shown in adult studies (female:male ratio of 6:1), female children have a higher risk of CFS although not to the same extent. The audit demonstrated no clear precipitating cause. There is association of viral infections with CFS. Unlike in adults, where less than 10% recover to pre-morbid levels, children with CFS have good prognosis with high remission when they are supported by a service that includes OT and paediatricians.